Determinants of foreign direct investment in Malaysia / Fazli Ahmad - Ahmad, Fazli (2017)
Foreign Direct Investment (FDI) shows important roles in boosting the economy of a country and development where foreign country set up their company bases into selected country to gain profit by taking the advantages of other factor such as low interest, trade openness where the investment from outside easily enter the market, or looking at the stability of the economy of the country. FDI promotes economy development through the injection of capital to the country and helps country faces capital shortage. As the country development have increase, it will indirectly improve the rate of unemployment where it helps to give out a job opportunity for the residents. In addition, FDI also helps in improving worker skill as the skilled worker from abroad with advance work skill will share their technology, idea, information and equipment. Malaysia economy have shown the economy growth performance are great from the past few decades depends on the FDI. FDI generates economic growth by increasing capital injection from outsources for development, promotion of export growth and creation of employment in Malaysia. Data from World Bank has shown a fluctuation of FDI inflow in Malaysia that started on 1996 to 2010 due to the Financial Crisis that give great impact to many country including Malaysia. High volatility of the FDI inflow of Malaysia have open up opportunities for the researchers to do research study on what factor that contribute to the changes of FDI. Researcher have come out with a regression to study the relationship between independent variables (economic growth, exchange rate, inflation rate and interest rate) and dependent variable (Malaysia FDI inflow) by using annual data from year 1980 to 2015. The empirical result from the study show that the independent variables of economic growth, interest rate and exchange rate is positively significant. In contrast, the independent of inflation is positively insignificant.